Analysis of Resistance to Bactericera cockerelli in Potato Germplasm: A Sustainable Approach (Innovation & Development in Engineering and Applied Science, 2025)
Bactericera cockerelli (Sulc) is the main vector of plant phloem-associated pathogens responsible for the potato purple top complex, a disease that can cause losses of up to 100% in potato crops. Chemical control methods, mainly based on insecticides, have proven to be inefficient due to the development of insect resistance. This problem highlights the need to implement sustainable strategies to mitigate its impact. One promising strategy is the genetic resistance of plants, specifically antibiosis, this type of resistance implies that plants negatively affect the insect's biology. In this context, the present study aimed to identify potato genotypes conserved by the National Roots and Tubers Program of the National Institute of Agricultural Research with antibiosis resistance characteristics against B. cockerelli, by means of a statistical analysis based on a complete factorial design. The evaluation considered the number of eggs oviposited on different days of evaluation in 9 wild species, 18 improved varieties, 15 native varieties and 18 promising clones. Genotypes with a marked resistance due to antibiosis were identified. These materials can contribute valuable genetic resources for breeding programs and the implementation of integrated crop management strategies, thus reducing dependence on pesticides that endanger human health and biodiversity.
Keywords: Bactericera cockerelli; resistance; potato; biodiversity; Precipitation